The Pathophysiologic Basis of Nuclear Medicine - Elgazzar, Abdelhamid H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book, now in its fourth edition, aims to promote a deeper understanding of the scientific and clinical basis of nuclear medicine and the new directions in medical imaging. The new edition has been revised and updated significantly to reflect recent changes and to ensure that the contents are in line with likely future directions. In addition to that, chapters have been reorganized in order to simplify the contents and to increase the readability. The book starts by providing essential information on general pathophysiology, cell biology and biologic effects of ionizing radiation followed by the mechanisms of radiopharmaceutical localization in different tissues and cells. This is followed by a series of chapters that covers all relevant organ systems presenting the basic knowledge of anatomy, physiology, and pathology and relating them to the clinical utilization of various scintigraphic modalities. The final chapter is devoted to the basis of therapeutic applications of nuclear medicine. The book will prove invaluable to all with an interest in the pathophysiologic basis of Nuclear Medicine, including nuclear medicine professionals, radiologists, surgeons, pediatricians and internal medicine physicians.
General Concepts of Pathophysiology -- Cell Biology and Biologic Effects of Ionizing Radiation -- Basis of Radiopharmaceutical Uptake -- Basis of Inflammation Imaging -- Basis of Musculoskeletal Imaging -- Basis of Endocrine System Imaging -- Basis of Genitourinary System Imaging -- Basis of Respiratory System Imaging -- Basis of Cardiovascular System Imaging -- Basis of Digestive System Imaging -- Basis of CNS Imaging -- Basis of Oncologic Imaging -- Basis of Therapeutic Radionuclide Therapy. .
Keywords: Nuclear medicine; Pathology; Nuclear Medicine; Pathology; Nuclear Medicine; Radionuclide Imaging